Science & Technology - Tang, Joyce (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
The objective of this course is to introduce a sociological conception of the nature of science and technology and of the scientific and engineering professions. The relationship between new technology and social change will also be explored. The course is designed for sociology majors and minors, but could be of interest and benefit to nonmajors as well.